Essential issues in symbolic interaction - Chen, Shing-Ling S.; Denzin, Norman K. (Studies in symbolic Interaction ;, 2024)
Over the course of more than 70 years, students of symbolic interactionism have demonstrated how a resourceful and conceptually rich perspective can generate variegated lines of research. However, many have expressed concerns over the sheer wealth and quantity of "lines of research" and the promotion of a "chaos" that lacks a cohesive focus on the fundamental issues, processes, and concepts that define the essence of symbolic interactionism. Answering David Maines' call for a forum to define and describe different lines of research, Volume 59 of Studies in Symbolic Interaction allows symbolic interactionists to demonstrate how and why their respective lines of research contribute to the quality and substance of symbolic interactionism. Examining key issues across their respective specializations, authors analyze their importance, historical development, and relevance to this field. Seeking a concise and substantial vision of symbolic interactionism, Essential Issues in Symbolic Interaction manifests the crucial research endeavors and key elements that contribute to the vitality of the interactionist theoretical framework.